Modelamiento estadístico para la predicción analógica de reservas en los bloques sometidos al proceso de inyección de agua en las Cuencas Valle Medio del Magdalena, Catatumbo y Llanos Orientales (2012)
The statistical model developed in this work was made to predict a water injection process, taking into account historical injection and production data, as well as static and dynamic characteristics of fields that have already went through this process. The forecasts were made based on historical settings obtained in OFM and organized in databases in Microsoft Excel. This information allows displaying the results of the process previously explained in an organanized way, for each one of the blocks belonging to the Middle Magdalena Valley, Llanos Orientales and Catatumbo basins. Based on the results obtained and by applying statistical methods, it was possible to predict the behavior of the declination in the analyzed fields and the similar ones that are prospective for applying the water injection process.